SPAN Website for Remote Intervention with Autistic Adolescents and Young Adults: Feasibility and Usability - Liron Lamash; Eynat Gal; Einat Yaar; Gary Bedell (MDPI AG, 2023)
Adolescents and young adults (AYA) with autism spectrum disorders (ASD) report less functional independence and social participation than their neurotypical peers. Remotely delivered interventions may allow autistic AYA to promote their independence, social participation, and wellbeing as they transition to adulthood. Social Participation and Navigation (SPAN) is a technology-based remotely delivered intervention initially developed for AYA with acquired brain injuries. The SPAN (website, application, and intervention manual) was modified to address the needs of AYA with autism (SPAN-ASD). This study examined the SPAN-ASD website and web application's feasibility and usability. Participants comprised 12 autistic AYA and 18 practitioners (all occupational therapists) with more than 1 year of experience in working with autistic AYA. All navigated the SPAN-ASD website and goal-management application. Practitioners completed the SPAN-ASD components and the Usefulness, Satisfaction, and Ease of Use questionnaires; AYA completed the System Usability Scale. The practitioners' average feasibility scores ranged from 4.30 to 4.68 (high); the overall usability score was 5.77 (good). The autistic AYA rated SPAN-ASD as a good, acceptable, and useful tool. Content analysis and item-level ratings indicated some needed improvements. Practitioners and autistic AYA perceived the SPAN-ASD website and application as highly feasible and usable, with excellent potential for technology-supported interventions.